Spatial Analysis of the CO Emission from Nineveh Governorate Using Remote Sensing Techniques and GIS - Ali, Sabah H.; Najemaden, Mohamed A. (Iraqi Journal of Science, 2021)
Carbon Monoxide (CO) has a significant indirect effect on greenhouse gasses due to its ozone and carbon dioxide precursor, and its mechanism of degradation involving the hydroxyl radical (OH) which control the oxidizing ability of the tropospheric. To understand the effect of human activities on atmospheric composition, accurate estimates of the sources of atmospheric carbon monoxide (CO) are necessary. MOPITT (Measurements of Pollution in the Troposphere) is a NASA Terra satellite instrument designed to allow both Thermal-Infra-Red (TIR) and Near-Infra-Red (NIR) observations to be used to collect vertical CO profiles in the Troposphere via the concept of correlation spectroscopy. The objective of the current study is to analyze and map the monthly, seasonal and annual trend of CO concentration for year 2016 in Nineveh governorate using the retrieved CO Surface Mixing Ratio Day mode of level 3, version 7 dataset. The dataset was downloaded from the National Aeronautics and Space Administration (NASA) operated GIOVANNI portal. The results of dataset analysis in GIS software showed many sources of carbon monoxide in Nineveh Governorate, which change with months and seasons of the year. Generally, the observed CO concentration levels in the southern and western of the governorate were more than in the northern and eastern parts. The annually average CO ranges from (115.374 ppbv) to (132.452 ppbv). Also, CO emissions and concentrations were higher in winter (128.638-157.567 ppbv) than summer season (97.144-106.515 ppbv).